PENYELESAIAN SENGKETA KONSUMEN OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DAN LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA DI SEKTOR JASA KEUANGAN (LAPS-SJK) - Sugandi Ishak (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
The estabilishment of alternative dispute settlement institutions in the financial service sector by financial services authorithy as if it wants to compete with the existence of consumer dispute settlement agency. The estabilishment institutions of alternative dispute settlement in the financial service sector on the basic of financial service authority regulatory law number 1 year 2014 on the financial service authority, while consumer dispute settlement agency formed by the law number 8 year 1999. Verdict generated by these two institutions are final and binding, however against the verdict institutions of alternative dispute settlement in the financial service sector cannot be impelemnted if the consumer does not accept the verdict, giving rise to the possibility for financial service businesses to submit district court (of justice). Another case with verdict of the consumer dispute settlement agency it can be objected in district court (of justice) by one of the parties does not accept the verdict. The prosecuting authority (competence) of the institutions of alternative dispute resolution financial service sector and consumer dispute resolution has not been regulation, so that dualism in handling consumer disputes settlement agency. This is evidenced by the many disputes between the consumer banking or non-banking and non-financial services businesses were marked by consumer dispute settlement agency. Therefore need for strict regulation regarding the authority or competence of an absolute judge of these two institutions and needs for improvement of the legislation to get around this legal weaknes shortcomings.Keywords: consumer dispute settlement agency, institutions of alternative dispute settlement in financial service sector, authority, dispute